2021
DOI: 10.3389/feart.2021.687382
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Reflection Images of Possible Mantle-Fluid Conduits and Basal Erosion in the 2011 Tohoku Earthquake Rupture Area

Abstract: Multi-channel seismic reflection and sub-bottom profiling data reveal landward-dipping normal faults as potential conduits for mantle-derived fluids in the coseismic slip area of the 2011 Tohoku earthquake (Mw9.0). Normal faults below the helium isotope anomaly sites appear to develop through the forearc crust (i.e., the seafloor sedimentary section and Cretaceous basement) and to evolve to lower dip angles as extension progresses deeper, potentially extending down to the mantle wedge, despite their intermitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Tsuji et al (2011) and JAMSTEC used different processing methods than Tsuru et al (2002), and uncertainty in depth conversions of seismic profiles may cause biases in estimating frictional strength, as we noted in the introduction. In particular, using the migrated-profile D6 of Park et al (2021), which is the nearest transect to that of Tsuji et al (2011), we obtained α and β values of 4.69° and 3.26°; we obtained μ b ' = 0.09 in D6, with the critical taper based on the parameters of Koge et al (2014). Now, our updated results for the Japan Trench highlight the usefulness of our α-μ b ' approximation.…”
Section: Application Example Of the α-μ B ' Approximation For The Jap...mentioning
confidence: 54%
“…Tsuji et al (2011) and JAMSTEC used different processing methods than Tsuru et al (2002), and uncertainty in depth conversions of seismic profiles may cause biases in estimating frictional strength, as we noted in the introduction. In particular, using the migrated-profile D6 of Park et al (2021), which is the nearest transect to that of Tsuji et al (2011), we obtained α and β values of 4.69° and 3.26°; we obtained μ b ' = 0.09 in D6, with the critical taper based on the parameters of Koge et al (2014). Now, our updated results for the Japan Trench highlight the usefulness of our α-μ b ' approximation.…”
Section: Application Example Of the α-μ B ' Approximation For The Jap...mentioning
confidence: 54%
“…The observation of widespread shallow normal faults cutting through the Neogene sedimentary cover of the margin had already been reported [von Huene and Lallemand, 1990] but not their deeper extent. In their interpretation, Park et al [2021] identified some of these at depths greater than 20 km. Their shallow dip suggests the reactivation of former splay faults into normal faults as similarly observed off Ecuador [Collot et al, 2008] or at the transition from Alaska and Aleutian subduction zones [Kahrizi et al, 2024].…”
Section: The Ne Japan Margin As a Case Studymentioning
confidence: 99%
“…It concerns both the penetration depth and the resolution of the data. Figure 1 is an example of the progress made, allowing the NE Japan margin to be imaged with unprecedented accuracy [Park et al, 2021]. The observation of widespread shallow normal faults cutting through the Neogene sedimentary cover of the margin had already been reported [von Huene and Lallemand, 1990] but not their deeper extent.…”
Section: The Ne Japan Margin As a Case Studymentioning
confidence: 99%
See 2 more Smart Citations